The 2nd International Conference on Advances in Mechanical Engineering - Khan, Muhammad; Hyder, Mohammad; Irfan, Muhammad; Masud, Manzar (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
The Second International Conference on Advances in Mechanical Engineering, ICAME-22, was held on 25th August, 2022 at the Mechanical Engineering Department of Capital University of Science and Technology. All articles underwent a rigorous single-blind peer review process. ICAME-22 accepted papers in the disciplines of experimental and computational fluid dynamics, thermodynamics, heat Ttransfer, machine and mechanisms, design, solid mechanics, manufacturing, production and industrial engineering, engineering management, technology management, renewable energy, environmental engineering, bioengineering, materials, failure analysis, and related fields.